The Urgency of Regulating the Measure of Violation in Terms of Sanctioning Notary - Iman, Zenza Bronica; Ruslijanto, Patricia Audrey; Jauharoh, Arini (NEGREI: Academic Journal of Law and Governance, 2024)
This study aims to analyze the urgency of legal ambiguity in determining the benchmark for imposing sanctions on notaries based on the Law on Notary Positions (UUJN). The UUJN regulates various sanctions for notaries who violate the law but does not provide clear guidelines regarding the criteria for imposing sanctions. This results in legal uncertainty and inconsistency in the enforcement of sanctions, as evidenced by the different sanctions imposed on two notaries, DS and MI, despite their similar violations. This research employs a normative juridical method with a statutory approach and a case approach. The results show that the ambiguity of norms in the UUJN has the potential to cause injustice in the enforcement of sanctions, as well as disrupt legal certainty and the integrity of the notary profession. In conclusion, a revision of the UUJN or the addition of supplementary regulations that include clearer and more proportional benchmarks for sanctioning is necessary. This will ensure justice and consistency in the application of sanctions, as well as uphold the integrity of the notary profession